PENGARUH KUALITAS PELAYANAN DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN PADA KULINER SOTO BETAWI GLOBE H. OJI DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Dea Nadiya; Dewi Kurniawati (Jurnal Riset Bisnis, 2025)
This study aims to analyze the influence of service quality and Word of Mouth (WOM) communication on purchasing decisions, with customer satisfaction as an intervening variable. The research was conducted on 100 consumers of Soto Betawi Globe H. Oji in Central Jakarta, using a quantitative approach and a survey method through Google Forms. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach via the SmartPLS 4 application. The results show that service quality and WOM have a positive and significant impact on customer satisfaction and purchasing decisions, and customer satisfaction is proven to mediate the influence of both variables. These findings recommend that culinary businesses focus on improving service quality and encouraging positive WOM to enhance customer satisfaction and loyalty.